Advances in the Management of Biliary Tract Cancers - Ciombor, Kristen Keon (2013)
Biliary tract cancers (BTC), though uncommon, are highly fatal malignancies, and current treatments fail to cure or control the majority of tumors. Given the complexity of the anatomy and often aggressive nature of the disease, multidisciplinary treatment, including palliation, is often required. However, systemic therapy with cytotoxics and/or targeted agents are routinely the mainstay of treatment for patients with advanced biliary tract cancers, and new targets and agents provide hope for this disease. This article focuses on recent advances in the management of biliary tract cancers, with a special focus on the molecular basis for current therapeutic investigation in this disease.